A bifunctional strategy for N-heterocyclic carbene-stabilized iridium complex-catalyzed N-alkylation of amines with alcohols in aqueous media. Issue 2 (20th December 2018) - Huang, Ming; Li, Yinwu; Liu, Jiahao; Lan, Xiao-Bing; Liu, Yan; Zhao, Cunyuan; Ke, Zhuofeng
Abstract : A bifunctional strategy for efficient Ir-catalyzed N -alkylation of amines and sulfonamides with alcohols under aqueous and base-free conditions. Abstract : Through the strategy of combining bifunctional 2-hydroxypyridine and a thermally stable N-heterocyclic carbene ligand, an Ir-catalyzed N -monoalkylation reaction has been developed in aqueous media under base-free conditions. This reaction proceeds smoothly with high yields of various aromatic amines and sulfonamides with a wide range of primary alcohols. Experimental and computational studies revealed a metal–ligand cooperative mechanism and its thermal stability during the bifunctional catalysis in aqueous media.